Student-centered learning approach in teaching basic grammar - Muhammad Buditama (Journal on English as a Foreign Language, 2017)
The study determined the effect of student-centered learning approach in teaching basic grammar of the tenth-grade students. Specifically, this study sought answers to following questions: 1). How does the result of the pre-test compare to that of post-test of the control and experimental groups? 2). Is there any significant difference in the results of the test between the control and experimental groups? 3). What is student-centered teaching guide in basic grammar that can be developed based on the findings of the study? It was applied an experimental research design in this study. The result in the post-test of the control and experimental groups showed that the computed the T value of 3.03 was higher than the tabular value of 2.03, at the degree of freedom of 34, at 5% level of significance. This condition rejects the null hypothesis that there is no significant difference in the mean scores in the post-test of the control and experimental groups. The student-centered teaching guide enhanced the students’ writing skill in the basic grammar of the tenth-grade students in the experimental group.